How I treat Philadelphia chromosome–positive acute lymphoblastic leukemia - Ravandi, Farhad (Blood, 2019)
The introduction of agents targeted at specific molecular events is changing the treatment paradigms in a number of malignancies. Historically, we have relied entirely on DNA-interactive, cytotoxic drugs for treating patients with leukemia. Increased understanding of the leukemic cell biology and pathogenesis, and the ways they evade the immune surveillance mechanisms, will likely lead to the development of more effective agents, and regimens less reliant on chemotherapy, able to achieve deep levels of disease eradication. In Philadelphia chromosome–positive acute lymphoblastic leukemia, the introduction of increasingly potent tyrosine kinas inhibitors (TKIs) has revolutionized therapy. These drugs have been established as the cornerstone of any therapeutic strategy in this disease, and a number of trials have better defined the best ways to incorporate them into the established paradigms. Despite using TKIs, we have continued to remain reliant on cytotoxic chemotherapy regimens and allogeneic hematopoietic cell transplant to achieve the best long-term outcomes. However, with the introduction of more potent TKIs and other novel agents, as well as better methods for monitoring minimal/measurable residual disease, we are entering an era where we hope to diminish our reliance on transplantation and cytotoxic chemotherapy in this disease.